Genomic Variants Among Threatened Acropora Corals. Issue 5 (1st May 2019) - Kitchen, Sheila A; Ratan, Aakrosh; Bedoya-Reina, Oscar C; Burhans, Richard; Fogarty, Nicole D; Miller, Webb; Baums, Iliana B
Abstract: Genomic sequence data for non-model organisms are increasingly available requiring the development of efficient and reproducible workflows. Here, we develop the first genomic resources and reproducible workflows for two threatened members of the reef-building coral genus Acropora . We generated genomic sequence data from multiple samples of the Caribbean A. cervicornis (staghorn coral) and A. palmata (elkhorn coral), and predicted millions of nucleotide variants among these two species and the Pacific A. digitifera . A subset of predicted nucleotide variants were verified using restriction length polymorphism assays and proved useful in distinguishing the two Caribbean acroporids and the hybrid they form (" A. prolifera "). Nucleotide variants are freely available from the Galaxy server (usegalaxy.org), and can be analyzed there with computational tools and stored workflows that require only an internet browser. We describe these data and some of the analysis tools, concentrating on fixed differences between A. cervicornis and A. palmata . In particular, we found that fixed amino acid differences between these two species were enriched in proteins associated with development, cellular stress response, and the host's interactions with associated microbes, for instance in the ABC transporters and superoxide dismutase. Identified candidate genes may underlie functional differences in how these threatened species respond to changing environments. Users can expand the presented analyses easily by adding genomic data from additional species, as they become available.